A Rare Hardware-related Complication after Deep Brain Stimulation: Two Cases of Twiddler’s Syndrome - Iroda Mammadinova; Seitzhan Aidarov; Nurtay Nurakay; Yerbol Makhambetov; Chingiz Nurimanov (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Twiddler’s syndrome is an uncommon complication of deep brain stimulation, arising from the inadvertent rotation of the implanted pulse generator, which results in lead coiling, displacement, or fracture. This results in stimulation failure and symptom recurrence, often necessitating surgical revision. While well-documented in cardiac devices, Twiddler’s syndrome remains infrequent in operations. Early diagnosis through radiographic imaging and impedance abnormalities is crucial for prompt intervention. We report two cases of Twiddler’s syndrome in patients with movement disorders: a 73-year-old male with Parkinson’s disease and a 55-year-old female with multifocal dystonia, both of whom had bilateral deep brain stimulation with left-sided dual-channel implanted pulse generator. After years of effective symptom control, both patients presented with worsening motor symptoms. Device examination revealed abnormal impedance readings, and imaging confirmed extensive lead coiling. Surgical revision was performed, including lead replacement and implanted pulse generator repositioning under the pectoralis fascia. Both patients demonstrated significant symptom improvement postoperatively, with restored impedance levels and functional recovery. Twiddler’s syndrome is a rare but critical complication of deep brain stimulation, leading to hardware failure and clinical deterioration. Early diagnosis through imaging and impedance monitoring is essential. Preventive strategies, including secure implanted pulse generator fixation and careful pocket sizing, are key to minimizing risk and improving patient outcomes.